The Resolution Process of Dopofileighoo (Elopement) Tradition in the Muna Ethnic at Muna Barat Regency, The Province of Southeast Sulawesi, Indonesia - Aso, La; Suraya, Rahmat Sewa; Iru, La; Suardika, I. Ketut; Taena, La; Hayari; Arman (Advances in Social Sciences Research Journal, 2022)
This study aims to describe the process of resolution of dopofileighoo (elopement) tradition in the Muna ethnic at Muna Barat Regency, the Province of Southeast Sulawesi, Indonesia because there are still many Muna people who do not understand the process of resolution of dopofileighoo (elopement) tradition so it needs to be studied. This study uses a qualitative description through the interview method continued with observations of people’s lives and document studies. The data of this study were analyzed descriptively, qualitatively, and interpretively. The results of this study showed that there are several stages in the process of resolution of dopofileighoo (elopement) tradition in the Muna ethnicat Muna Barat Regency, the Province of Southeast Sulawesi, Indonesia. Those stages are as follows: (1) O hukumu (A man whose task is receiving the bride and groom candidates and responsible to handle them until finishing the conducting of the marriage processing in the dopofileighoo (elopement) tradition in the Muna ethnic) receives the two bride and groom candidates; (2) Doing polele (Informing the bride candidate’s parents); (3) Dengkoraghoo adhati (Settling the customs); (4) Kafotangkano agama (Religion settlement of administration according to Islam religion), and (5) Kafokawi (Conducting the wedding processing)